Five-Year Evaluation of Chronic Diseases in Hamadan, Iran: 2005-2009 - MM Majzoobi; B Amiri; RS Mir-Moeini; R Zamani; J Poorolajal; H Erfani; SJ Bathaei (Tehran University of Medical Sciences, 2012)
Background: Now the increasing growth of chronic diseases is the major health challenge worldwide. This survey was conducted to assess noncommunicable diseases related risk factors.methods: A population-based cross sectional study was conducted in 2005 and repeated annually by 2009 in Hamadan province, the west of Iran using two-stage cluster sampling method. A total sample of 6500 subjects 15 to 64 years old were enrolled.Results: The total prevalence of cigarette smoking was 18% [95% CI 17% to 19%], 35.1% in men versus 1.1% in women. The smokers consumed on average 15 cigarettes per day. Almost 26.3% [95% CI 24.8% to 27.7%] of the target population eat five or more servings of fruits and vegetables per day; 52.8% [95% CI 51.2% to 54.3%] had work related physical activity; 28.1% [95% CI 26.7% to 29.4%] had physical activity during leisure time; 80.3% [95% CI 79.0% to 81.5%] had transportation related physical activity; 47.2% [95% CI 46.0% to 48.4%] were either overweight or obese; 8.1% [95% CI 7.1% to 9.2%] had impaired fasting blood sugar or were confirmed diabetes; 33.7% [95% CI 31.9% to 35.5%] had hypercholesterolemia; and 15.6% [95% CI 13.0% to 18.3%] had hypertriglyceridemia. There was a statistically significant association of age and gender with body mass index, systolic and diastolic hypertension, hyperglycemia, hypercholesterolemia and hypertriglyceridemia.Conclusions: The evidences of the present survey promise a silent progressive epidemic of chronic diseases among Iranian citizens that may lead to an increasing growth of noncommunicable diseases in the next decade.